Advances in model-based software testing (A-MOST). - Dalal, Siddhartha R.
This is a summary of the Advances in Model-Based Software Testing (A-MOST) workshop held on May 15-16, 2005, in St. Louis, Missouri. The workshop had approximately 40 participants. The goals of this workshop were to offer a comprehensive overview of model-based testing to the ICSE community, and bring the researchers and practitioners together to discuss advances, applications, and the complex problems yet to be solved in model-based testing. The workshop was lively and maintained participant interest for the entire two-day program. A brief summary based upon agenda items is provided. Details on the workshops are archived at http://aetgweb.argreenhouse.com.
Keywords: General literature; Introductory and survey; Software; Software engineering; Software / Program Verification; Model checking; Testing and debugging; Design; Documentation